EXTRACTION OF LEFT VENTRICULAR CONTOURS FROM VENTRICULOGRAMS WITH LABELING OF IMAGE PIXELS BY ACTIVE CONTOURS - Polyakova, Marina (International Journal of Computing, 2014)
The method of the extraction of left ventricular contours is developed for ventriculograms which obtained by radiological research of heart with the angiographic system. The proposed method includes the underlining of left ventricular contours through the repagular wavelet transform and labeling the pixels of image by active contours that reduced the error of detection of the edge and the area of left ventricle.